Adaptive myriad filtering algorithms for removal of nonstationary noise in electrooculograms - Tulyakova, N.; Trofymchuk, O. (Проблеми керування та інформатики, 2023)
This article presents adaptive algorithms for real-time nonlinear filtering of non-stationary noise in EOG signals using noise- and signal-dependent filter switching, which is more appropriate for processing the local neighborhood of the current sample of the input signal. One of the algorithms is based on myriad and weighted impulse response (IR) hybrid myriad filters. It proposes replacing the median operation of the myriad with adaptive switching of window length and linearity parameter values. Another algorithm adaptively switches between weighted IR hybrid median filters and averaging filters with different window lengths, ensuring simpler calculations and high performance. Numerical simulations were conducted to evaluate filtering quality based on the mean square error and signal-to-noise ratio criteria for a modeled signal at various levels of Gaussian noise. The results show high-quality suppression of non-stationary noise in EOG. У статті представлено адаптивні алгоритми нелінійної фільтрації нестаціонарного шуму в реальному часі в сигналі ЕОГ за допомогою шумо- та сигнал-залежного перемикання фільтру, більш придатного для обробки локального околу поточного відліку вхідного сигналу. Один із алгоритмів базується на міріадних і зважених КІХ (кінцева імпульсна характеристика)-гібридних міріадних фільтрах. У ньому пропонується замінити медіанну операцію міріадою з адаптивним перемиканням довжини вікна та значень параметру лінійності. Інший алгоритм адаптивно перемикає зважені КІХ-гібридні медіанні фільтри та фільтри усереднення з різною довжиною вікна, забезпечуючи простіші обчислення та високу швидкодію. Проведено чисельне моделювання для оцінки якості фільтрації за критеріями середньоквадратичної похибки та співвідношення сигнал/шум для модельного сигналу при різних рівнях гаусова шуму. Отримані результати свідчать про високу якість заглушування нестаціонарного шуму в ЕОГ.